A study of prescribing pattern of drugs in patients of cardiovascular emergencies at a tertiary care hospital of Western Maharashtra - Vakade, Kiran P.; Thorat, Vandana M.; Khanwelkar, Chitra C.; Jadhav, Sujata A.; Sanghishetti, Vijayprasad M. (International Journal of Research in Medical Sciences, 2016)
Background: The main objective of drug utilization research is to assess the rationality of drug use. Recently it has been found that cardiovascular disease is the most frequent cause of morbidity and mortality throughout the world. The objective of present study was to focus on the trends in prescribing patterns of most frequently treated cardiovascular emergencies. Methods: A retrospective descriptive study was carried out in cardiovascular emergency patients. From the medical records the following data was collected: Distribution of cardiovascular emergencies (age and sex wise), most common cardiovascular emergencies treated, outcome of each patient, average duration of stay in the hospital and drugs prescribed per patient, correlation of clinical outcome with treatment if possible, drug utilization trend in cardiovascular emergencies. From the data, master chart was prepared for data analysis. Results: Total 82 patients case records were studied. Myocardial infarction (50%) was the most common cardiovascular emergency treated during study period followed by unstable angina (36.58%). Male to female ratio was 1.83. Average hospital stay was found 5.75 days. The average number of drugs per patient was 8.4. Hypertension (42.24%) and diabetes mellitus (19.51%) were the most common comorbidities found associated with cardiovascular emergencies. Aspirin clopidogrel combination (80.49%), enoxaparin (75.61%), atorvastatin (73.17%), glyceryl trinitrate (73.17%) were the most commonly prescribed drugs. The utilization rate of ACE inhibitors and ARBs (56.10%) was found higher than that of beta blockers (28.05%). Stool softeners (52.46%) and anxiolytics (28.58%) were the most commonly used non-cardiovascular drugs. Improvement was seen in 82.93% patients. Conclusions: Protocol of management strategy of cardiovascular emergencies in our tertiary care hospital was found near to standard recommended guidelines. Keywords: